Проблеми і можливості формування системи управління економічною безпекою у закладах освіти - Завербний, А.С.; Пушак, Г.І. (Економічний вісник Донбасу, 2025)
У статті висвітлено основні проблеми і можливості формування системи управління економічною безпекою у закладах освіти. Сучасна українська система освіти потребує не лише модернізування, але й створення механізмів захисту її ресурсів. Саме тому висвітлена проблематика є актуальною. Цілями статті є дослідження проблем, виявлення та обґрунтування перспектив і можливостей для формування дієвої та ефективної системи управління економічною безпекою у закладах освіти. В статті застосовано наступні методи дослідження: аналіз та синтез. Проведено огляд літературних джерел за проблематикою формування систем управління економічною безпекою. На основі систематизування наукових тлумачень запропоновано визначення сутності «економічна безпека закладів освіти», під яким розуміється стан захищеності освітніх установ, зокрема їх фінансово-економічних інтересів, від внутрішніх, зовнішніх загроз, що можуть негативно вплинути на їх фінансову стабільність, конкурентоспроможність, можливості виконувати свої функції а також здатність закладів протидіяти зазначеним загрозам, забезпечуючи стійке і гармонійне розвивання. Серед ключових проблем формування системи управління економічною безпекою закладів освіти виділено наступні: фінансову нестабільність, кадрові ризики, інформаційні загрози, організаційні слабкості. Їх подолання можливе шляхом диверсифікування фінансування (не зосереджуватися виключно на державному фінансуванні), розвивання власного кадрового потенціалу, впровадження сучасних інформаційних технологій захисту, створення дієвої інституційної бази. Розвинуто процеси формування системи управління економічною безпекою у закладах освіти. Запропонована в роботі система володіє циклічним характером, передбачаючи послідовне проходження від аналізування ризиків до впровадження заходів, подальшого їх удосконалення, що дозволятиме закладам освіти підтримувати економічну стабільність, зменшувати вплив негативних факторів, підвищувати рівень власної конкурентоспроможності у сучасному мінливому освітньому середовищі. Реалізування пропонованих в статті заходів забезпечуватиме підвищення рівня стійкості освітніх закладів, сприятиме розвиванню конкурентоспроможної національної системи освіти. The article examines the principal challenges and opportunities associated with the development of an economic security management system in educational institutions. The contemporary Ukrainian education system requires not only comprehensive modernization but also the establishment of mechanisms aimed at safeguarding its resources. Accordingly, the focus of this study is both timely and relevant. The purpose of the article is to investigate existing challenges, to identify and substantiate potential prospects and opportunities for the creation of an effective and efficient system of economic security management within educational institutions. The methodological framework of the research is based on the application of analysis and synthesis. A review of scholarly literature addressing the formation of economic security management systems has been undertaken. On the basis of systematizing existing academic interpretations, the article proposes a definition of the concept “economic security of educational institutions”. It is understood as the state of protection of educational establishments, particularly their financial and economic interests, from internal and external threats that may adversely affect their financial stability, competitiveness, ability to perform institutional functions, and their overall capacity to counter such threats, thereby ensuring sustainable and balanced development. The study identifies several key challenges in establishing an economic security management system in educational institutions, including financial instability, human resource risks, informational threats, and organizational weaknesses. Addressing these challenges requires a set of measures such as the diversification of funding sources (avoiding excessive reliance on state financing), the development of internal human capital, the implementation of advanced information security technologies, and the establishment of a robust institutional framework. Furthermore, the article advances the conceptualization of the processes underpinning the formation of an economic security management system in educational institutions. The proposed system is cyclical in nature, providing for a sequential progression from risk assessment to the implementation of protective measures and their subsequent improvement. This cyclical approach enables educational institutions to sustain economic stability, mitigate the influence of adverse factors, and enhance their competitiveness in the contemporary and rapidly changing educational environment. The implementation of these measures is expected to strengthen the resilience of educational institutions and contribute to the advancement of a competitive national system of education.